An examination and evaluation of intention to stay or leave scale by expert reviewers - Ismail, Wan Ismahanini; Mohd Rasdi, Roziah; Ibrahim, Rahinah; Abu Samah, Bahaman (Faculty of Educational Studies, Universiti Putra Malaysia, 2016)
It is crucial to develop a scale that can measure existing medical academics’ intention to stay or leave, as there are an increasing number of medical academics across grades who have resigned from public universities. For this study, the key dimensions in the scale were generated from Belief-Desire-Intention (BDI) model and Integrated Behavioural Model (IBM). Each item in the scale was not created solely from related theories and model but also extracted from literature reviews and promotional guidelines for medical academics. All the items derived from previous research were modified to reflect the context of academic medicine. Rasch model analysis provides systematic evidence of one of the aspects of construct validity that is content validity for the five dimensions with 52 items. All the items will be maintained for the next test. Four items will be modified based on experts’ comments with one additional item for Part C or under normative beliefs dimension. These results generate an important step towards the development of guidelines for use especially by university administrators in understanding the product obtained from the scale.